2022
DOI: 10.3892/etm.2022.11780
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑143‑3p levels are reduced in the peripheral blood of patients with gestational diabetes mellitus and influences pancreatic β‑cell function and viability

Abstract: Pancreatic β-cell dysfunction has been demonstrated to mediate key roles in the pathogenesis of gestational diabetes mellitus (GDM). Accumulating evidence has supported the functional involvement of microRNAs (miRNAs) in various types of diabetes, including GDM. However, the detailed biological effect of miRNAs in pancreatic β-cell dysfunction remains poorly understood. In the present study, microarray data of miRNAs in the blood plasma of patients with GDM were retrieved from the Gene Expression Omnibus datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…However, contradictory data attested up-regulation of miR-132 expression in several T 2 D models [ 68 ]. Furthermore, mir-132 has been found increased in both EVs in early gestation and placenta exosomes in gestational diabetes patients [ 69 ], while in plasma from second-trimester gestational diabetes patients was insignificantly [ 70 ]. Two other studies performed on a large group of patients found miR-132 decreased in gestational diabetes pregnancies [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, contradictory data attested up-regulation of miR-132 expression in several T 2 D models [ 68 ]. Furthermore, mir-132 has been found increased in both EVs in early gestation and placenta exosomes in gestational diabetes patients [ 69 ], while in plasma from second-trimester gestational diabetes patients was insignificantly [ 70 ]. Two other studies performed on a large group of patients found miR-132 decreased in gestational diabetes pregnancies [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, miR-143 regulation may be partially responsible for placental mitochondrial dysfunction in GDM. Additionally, miR-143-3p inhibits the Tak1/NF-κB pathway, thereby preventing pancreatic β-cell dysfunction ( 120 ).…”
Section: Gestational Diabetes and Metabolic Reprogrammingmentioning
confidence: 99%
“…Downregulation of miR-143-3p levels was found in plasma samples from 30 pairs of GDM patients and healthy women. Overexpression of miR-143-3p in HG-treated MIN6 cells showed that it inhibited the TAK1/NF-κB signaling pathway to promote cell viability and insulin secretion and prevent pancreatic β-cell dysfunction [ 70 ]. Dysregulation of miRNAs in serum may also regulate trophoblast function through genes and related pathways.…”
Section: Role Of Ncrnas In Gdmmentioning
confidence: 99%